2009
DOI: 10.1159/000201790
|View full text |Cite
|
Sign up to set email alerts
|

Course and Outcome of Dialysis Pericarditis in Diabetic Patients Treated with Maintenance Hemodialysis

Abstract: Introduction: This observational study investigated the course and outcome of dialysis pericarditis in diabetic dialysis patients, as previous reports found that in contrast to uremic pericarditis, which responds in most cases to intensive hemodialysis, dialysis pericarditis resolves with intensification of hemodialysis in fewer cases. Methods: From 2002 through 2006, 88 maintenance hemodialysis patients (47 diabetic and 41 non-diabetic) were referred for management of dialysis pericarditis. Results: Dialysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Taiwan continues to have the highest incidence and prevalence of ESRD in the world (15)(16)(17). According to the US Renal Data System in 2009 (15), incidence rates of reported ESRD are greatest in Taiwan, at 415 per million population in 2007, followed by Mexico, USA, Japan, and Shanghai.…”
mentioning
confidence: 99%
“…Taiwan continues to have the highest incidence and prevalence of ESRD in the world (15)(16)(17). According to the US Renal Data System in 2009 (15), incidence rates of reported ESRD are greatest in Taiwan, at 415 per million population in 2007, followed by Mexico, USA, Japan, and Shanghai.…”
mentioning
confidence: 99%
“…Few studies have evaluated the optimal time of pericardial drainage, however, most authors necessarily state the indication for emergency drainage in the event of clinical or ultrasound signs of tamponade [25].…”
Section: Discussionmentioning
confidence: 99%
“…In a Cochrane review of published literature on the use of colchicine in pericarditis, Alabed et al compared the effect of colchicine with indo-methacin and corticosteroids and concluded it is effective in recurrent pericarditis, but this was based on a small number of trials [ 19 ]. Overall, prognosis of uremic pericarditis is excellent, with a survival rate of 85–90% [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%